A real-time ultrasound-guided supraclavicular approach to the brachiocephalic vein to prevent Hickman catheter bending and occlusion - Yamamoto, Tomohiro; Arai, Yuhki; Schindler, Ehrenfried (Anestezjologia Intensywna Terapia, 2021)
The infraclavicular approach (subclavian approach) to the central vein is most often selected for implantation of a tunnelled Hickman/Broviac catheter because central venous catheter (CVC) insertion into the upper body is optimal considering patient comfort as well as the risk of infection [1] and intravenous thrombosis [2, 3]. However, the actual puncture site for a real-time ultrasound-guided infraclavicular axillary vein approach is at the level of the axillary vein in a much more lateral location than that for the traditional landmark infraclavicular approach to the subclavian vein. This is because an optimal view of the subclavian vein is difficult to obtain with a real-time ultrasound-guided technique, as the ultrasound beam is restricted by the clavicle [4]; the younger the patient, the greater would be its influence because of the width of the ultrasound probe. As a result, Hickman/Broviac catheter bending due to a sharply curved angle in the subcutaneous tunnel may occur when the subcutaneous tunnel exit needs to be created inside the patient’s nipple to obtain sufficient tunnel length, especially in young paediatric patients. When the internal jugular vein is chosen as an alternative puncture site, adverse events of catheter bending and occlusion may occur because the puncture direction to the target vein and the direction of the subcutaneous tunnel become very steep [5].